Metal-free catalyst for acetylene hydrochlorination reaction and preparation method and application thereof
Through the magnesium thermal reduction reaction, doping silicon oxide in the mixture of carbon dioxide and nitrogen gas, a composite carbon-based catalyst with porous carbon-nitrogen coated silicon oxide was prepared, which solved the problems of low activity and poor stability of metal-free catalysts, and achieved efficient acetylene hydrogen chlorination reaction and carbon emission reduction.
Patent Information
- Application Number
- CN202310258221.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The existing metal-free catalysts have low activity and poor stability in the acetylene hydrochlorination reaction, and it is difficult for traditional nitrogen doping methods to achieve uniform distribution of nitrogen and high mechanical strength of the material.
The magnesium thermal reduction reaction is used to dopant silicon oxide in the mixture of carbon dioxide and nitrogen to prepare a composite carbon-based catalyst with porous carbon-nitrogen coated silicon oxide, and the high specific surface area and rich mesoporous structure of the catalyst are achieved by regulating the process conditions.
The catalytic activity and stability of the catalyst are significantly improved, and excellent acetylene conversion and vinyl chloride selectivity are shown in the acetylene hydrochlorination reaction, while achieving carbon emission reduction and high-value utilization of carbon dioxide.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a metal-free catalyst for acetylene hydrochlorination reaction and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the world's five major general-purpose resins. It is inexpensive and has the advantages of high strength and corrosion resistance. It is widely used in industry, agriculture, construction, science and technology. PVC is synthesized from vinyl chloride monomer (VCM) through polymerization reaction. The methods for producing VCM include acetylene method, ethylene method, ethylene oxychlorination method and ethane oxychlorination method. At present, the main method for synthesizing VCM in my country's industry is acetylene method, that is, the reaction of acetylene and hydrogen chloride. The catalyst system used in the industrial acetylene method is a mercury-based catalyst supported by activated carbon. However, the lethal toxicity and high volatility of mercury pose a serious threat to humans and the environment. The development of mercury-free catalysts is imminent.
[0003] Mercury-free catalysts include precious metal catalysts, non-precious metal catalysts and non-metal catalyst systems. Among them, metal-free catalysts do not contain metal elements, and waste catalysts are easy to handle. They are newer green and environmentally friendly catalyst systems. However, metal-free catalysts currently generally have the problem of low activity and poor stability. How to further improve the activity and stability of catalysts is the key to the development of metal-free catalysts.
[0004] Nitrogen doping is considered to be the most effective modification method. Numerous literatures show that: ① The introduction of nitrogen creates unpaired electron defect sites between the graphite layers of carbon, anchoring the active components and promoting the dispersion of particles; ② Nitrogen atoms have special electron orbits and can provide a pair of extranuclear electrons to modify the electronic structure of the catalyst; ③ Nitrogen forms different types of nitrogen-containing functional groups on the surface of carbon materials, improving the adsorption capacity of reactants.
[0005] A journal article ("Preparation of nitrogen-doped mesoporous carbon by in-situ doping and its performance in acetylene hydrochlorination reaction", Yang Yong et al., Journal of Catalysis, Issue 8, 2016) reported a one-step in-situ urea-doped nitrogen-doped mesoporous carbon preparation method. The results showed that the in-situ synthesis method can effectively dope nitrogen into the skeleton. As the amount of urea increased during the preparation process, the nitrogen content in the obtained nitrogen-doped mesoporous carbon increased, up to 3.6wt%. The nitrogen doping effect of the post-treatment method was poor, and the nitrogen content of the material was only 0.2wt%. XPS testing further showed that the one-step in-situ method can obtain nitrogen-doped mesoporous carbon with graphite-type nitrogen dominating, accounting for about 70%. The contents of graphite nitrogen, pyridinic nitrogen and pyrrolic nitrogen in the nitrogen-doped mesoporous carbon prepared by post-treatment are not much different. The catalytic performance of nitrogen-doped mesoporous carbons synthesized by different methods in the acetylene hydrochlorination reaction was evaluated. The results showed that the activity of nitrogen-doped mesoporous carbons, whether prepared by in-situ synthesis or post-treatment, was improved to a certain extent compared with that of mesoporous carbons. The introduction of nitrogen can effectively improve the acetylene hydrochlorination performance of the material. The catalytic performance of nitrogen-doped mesoporous carbons prepared by in-situ synthesis in the acetylene hydrochlorination reaction is much higher than that by post-treatment. For nitrogen-doped mesoporous carbons synthesized in situ, within a certain range, the catalytic activity increases with the increase of nitrogen content, but when the amount of urea is too high, although the nitrogen content increases, the catalytic activity decreases, which is attributed to the collapse of the pore structure and the decrease in specific surface area.
[0006] The patent (CN108246340B) relates to a method for preparing a metal-free catalyst for the fixed-bed acetylene hydrochlorination to synthesize vinyl chloride and its use method. Compared with other metal-free catalysts prepared by "impregnation-calcination", the nitrogen content in the catalyst is increased by in-situ doping combined with ammonia treatment. The specific surface area of the catalyst is effectively increased by calcining the precursor with polytetrafluoroethylene under a special heating system. At the same time, the proportion of effective active sites and the number of oxygen-containing functional groups on the surface are increased by co-doping with nitrogen and sulfur and oxidation treatment. The metal-free catalyst has high activity and excellent selectivity in the reaction of preparing vinyl chloride by acetylene hydrochlorination in a fixed bed. The preparation method is green and environmentally friendly, with a wide source of raw materials and low cost. It can replace the toxic mercuric chloride catalyst and has broad application prospects in industrial production.
[0007] The nitrogen doping methods reported so far often use the impregnation and roasting method. However, this method cannot effectively achieve the uniform distribution of doped nitrogen, and has low mechanical strength and uncontrollable pore structure. Therefore, how to balance the above issues is a technical problem and difficulty that needs to be solved in the development of metal-free catalysts.
[0008] Considering that the main component of metal-free catalysts is carbon materials, how to select the carbon source is also a key factor in catalyst preparation. Converting carbon dioxide into various carbon materials is a technology that has gradually developed in recent years. Combined with the current domestic carbon emissions, this technology is expected to become an important technical route for preparing carbon materials. Therefore, how to controllably prepare carbon materials using carbon dioxide as a carbon source is a difficult point in achieving high-value utilization of carbon dioxide. Summary of the invention
[0009] The present invention aims at the problems existing in the prior art and provides a metal-free catalyst for acetylene hydrochlorination reaction and a preparation method and application thereof. The preparation method of the metal-free catalyst of the present invention is simple, can achieve uniform nitrogen doping, and has a high specific surface area, rich mesoporous structure, and good mechanical strength, and exhibits excellent catalytic activity and stability in acetylene hydrochlorination reaction. In addition, the preparation process consumes a large amount of carbon dioxide, which has significant significance for carbon emission reduction.
[0010] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides a metal-free catalyst for acetylene hydrochlorination reaction, characterized in that the metal-free catalyst is a composite carbon-based catalyst of porous carbon-nitrogen-coated silicon oxide; the metal-free catalyst uses magnesium powder and silicon-containing oxide as raw materials, and is obtained by magnesium thermal reduction reaction in a mixture of carbon dioxide and nitrogen, undergoing doping reaction and post-treatment.
[0011] Magnesium powder reduces CO2 to C through magnesium thermal reaction, and the corresponding Mg generates MgO, which consumes a large amount of greenhouse gases, achieving carbon emission reduction while realizing high-value utilization of carbon dioxide.
[0012] In a preferred embodiment, the silicon-containing oxide is any one or more of nano silicon oxide, talcum powder, and magnesium trisilicate hydrate; and the mass ratio of the magnesium powder to the silicon-containing oxide is 5-100:1.
[0013] In a preferred embodiment, the volume percentage of carbon dioxide in the mixed gas of carbon dioxide and nitrogen is 10%-80%.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned metal-free catalyst, comprising the following steps:
[0015] (1) Magnesium powder and silicon-containing oxide are fully mixed and placed in a tube furnace, the tube furnace is heated to a specified temperature under an inert gas, and then a mixture of carbon dioxide and nitrogen is introduced to react, and after a certain period of time, the inert gas is switched and the temperature is lowered to obtain a black powder;
[0016] (2) The black powder is immersed in an acidic solution, then washed with deionized water until it becomes neutral, and then dried to obtain the metal-free catalyst.
[0017] In a preferred embodiment, the heating rate of the tube furnace is 2-20°C / min, and the treatment temperature is 400-1200°C.
[0018] In a preferred embodiment, the inert gas is any one or more of helium and argon; a mixed gas of carbon dioxide and nitrogen is introduced into the tubular furnace for 0.2-10 hours.
[0019] In a preferred embodiment, the acidic solution is one or more of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, phosphoric acid, and perchloric acid, the molar concentration of the acidic solution is 0.5%-50%, the soaking temperature is 20-80°C, and the soaking time is 0.5-5h.
[0020] In a preferred embodiment, the drying temperature is 40-120° C., and the drying time is 2-48 hours.
[0021] In a third aspect, the present invention provides the use of the above-mentioned metal-free catalyst in the acetylene hydrochlorination reaction.
[0022] In a preferred embodiment, the reaction temperature of the acetylene hydrochlorination reaction is 150-250°C, and the acetylene space velocity is 5-300h -1 , the molar ratio of hydrogen chloride to acetylene is 1:1-1.5:1.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The metal-free catalyst of the present invention uses carbon-nitrogen materials to dope silicon oxide, which greatly improves the mechanical strength of the catalyst and can solve the problems of the existing industrial catalysts being difficult to shape and easy to pulverize;
[0025] (2) The present invention can control the structure and physical properties of the carbon-nitrogen layer by regulating the temperature and atmosphere of the tube furnace;
[0026] (3) The present invention uses CO2 as a carbon source to synthesize carbon materials through magnesium thermal reaction, consumes a large amount of greenhouse gases, achieves carbon emission reduction and realizes high-value utilization of carbon dioxide. DETAILED DESCRIPTION
[0027] It is worth noting that the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0028] Example 1
[0029] Weigh 50g of magnesium powder and 5g of talcum powder, mix them thoroughly, place them in a corundum crucible, and put them in a tubular furnace. Under an argon atmosphere, heat the tubular furnace to 600°C at 5°C / min, then switch to a 50% CO2 and nitrogen mixture, keep it for 2h, then switch to argon and cool it to room temperature. Take out the black powder, put it in a beaker and add enough 10% dilute hydrochloric acid, stir and soak it at room temperature 20°C for 2h, then wash and filter it, and then place it in a 100°C oven to dry for 12h to obtain a metal-free catalyst A. Take 5mL of catalyst A, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200°C, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200°C and 30h -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0030] Example 2
[0031] Take 50g of magnesium powder and 5g of talcum powder, mix them thoroughly, put them in a corundum crucible, and put them in a tubular furnace. Under an argon atmosphere, heat the tubular furnace to 700℃ at 5℃ / min, then switch to a 50% CO2 and nitrogen mixture, keep it for 2h, then switch to argon and cool it to room temperature. Take out the black powder, put it in a beaker and add enough 10% dilute hydrochloric acid, stir and soak it at room temperature 20℃ for 2h, then wash and filter it, and then place it in a 100℃ oven to dry for 12h to obtain a metal-free catalyst B. Take 5mL of catalyst B, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200℃, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200℃ and 30h -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0032] Example 3
[0033] Take 50g of magnesium powder and 5g of talcum powder, mix them thoroughly, put them in a corundum crucible, and put them in a tubular furnace. Under an argon atmosphere, heat the tubular furnace to 800℃ at 5℃ / min, then switch to a 50% CO2 and nitrogen mixture, keep it for 2h, then switch to argon and cool it to room temperature. Take out the black powder, put it in a beaker and add enough 10% dilute hydrochloric acid, stir and soak it at room temperature 20℃ for 2h, then wash and filter it, and then place it in a 100℃ oven to dry for 12h to obtain a metal-free catalyst C. Take 5mL of catalyst C, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200℃, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200℃ and 30h -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0034] Example 4
[0035] Take 50g of magnesium powder and 10g of talcum powder, mix them thoroughly, put them in a corundum crucible, and put them in a tubular furnace. Under an argon atmosphere, heat the tubular furnace to 800℃ at 5℃ / min, then switch to a 50% CO2 and nitrogen mixture, keep it for 2h, then switch to argon and cool it to room temperature. Take out the black powder, put it in a beaker and add enough 10% dilute hydrochloric acid, stir and soak it at room temperature 20℃ for 2h, then wash and filter it, and then place it in a 100℃ oven to dry for 12h to obtain a metal-free catalyst D. Take 5mL of catalyst D, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200℃, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200℃ and 30h -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0036] Example 5
[0037] Take 50g of magnesium powder and 5g of nano-silicon oxide, mix them thoroughly, place them in a corundum crucible, and put them in a tubular furnace. Under an argon atmosphere, heat the tubular furnace to 800℃ at 5℃ / min, then switch to a 50% CO2 and nitrogen mixture, keep it for 2h, then switch to argon and cool it to room temperature. Take out the black powder, put it in a beaker and add enough 10% dilute hydrochloric acid, stir and soak it at room temperature of 20℃ for 2h, then wash and filter it, and then place it in a 100℃ oven to dry for 12h to obtain a metal-free catalyst E. Take 5mL of catalyst E, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200℃, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200℃ and 30h -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0038] Example 6
[0039] Take 50g of magnesium powder and 5g of nano-silicon oxide, mix them thoroughly, place them in a corundum crucible, and put them in a tubular furnace. Under an argon atmosphere, heat the tubular furnace to 800°C at 5°C / min, then switch to a 20% CO2 and nitrogen mixture, keep it for 2h, then switch to argon and cool it to room temperature. Take out the black powder, put it in a beaker and add enough 10% dilute hydrochloric acid, stir and soak it at room temperature of 20°C for 2h, then wash and filter it, and then place it in a 100°C oven to dry for 12h to obtain a metal-free catalyst F. Take 5mL of catalyst F, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200°C, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200°C and 30h -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0040] Comparative Example 1
[0041] Take 50g of magnesium powder and place it in a corundum crucible, and put it into a tubular furnace. Under an argon atmosphere, the tubular furnace is heated to 800℃ at 5℃ / min, and then switched to a pure CO2 mixed gas. After maintaining for 2h, switch to argon and cool to room temperature. Take out the black powder, put it in a beaker and add a sufficient amount of 10% dilute hydrochloric acid. Stir and soak it at room temperature of 20℃ for 2h, then wash and filter it, and then place it in a 100℃ oven to dry for 12h to obtain a metal-free catalyst C1. Take 5mL of catalyst C1, load it into a fixed bed reactor, pass nitrogen gas to heat it to 200℃, dry it for 1h, then pass hydrogen chloride to activate it for 1h, and then pass a mixture of hydrogen chloride and acetylene at 200℃ and 30h. -1 The reaction was carried out under the reaction conditions of HCl / C2H2 volume ratio of 1.08.
[0042] The catalyst evaluation is shown in Table 1.
[0043] Table 1
[0044]
[0045]
[0046] As can be seen from Table 1, the metal-free catalyst prepared in the embodiment of the present application has a high acetylene conversion rate in the acetylene hydrochlorination reaction. -1 Under the conditions of acetylene space velocity, the acetylene conversion rate is greater than 80%, and the vinyl chloride selectivity is greater than 99%.
[0047] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A metal-free catalyst for acetylene hydrochlorination, characterized in that: The metal-free catalyst is a composite carbon-based catalyst of porous carbon-nitrogen-coated silicon oxide; the metal-free catalyst uses magnesium powder and silicon-containing oxide as raw materials, and is obtained by magnesium thermal reduction and doping reaction and post-treatment in a mixture of carbon dioxide and nitrogen; the volume percentage of carbon dioxide in the mixture of carbon dioxide and nitrogen is 10%-80%; the mass ratio of magnesium powder to silicon-containing oxide is 5-10:1; and the reaction temperature is 600-800°C.
2. The metal-free catalyst according to claim 1, characterized in that The silicon-containing oxide is any one or more of nano silicon oxide, talcum powder, and magnesium trisilicate hydrate.
3. The method for preparing a metal-free catalyst according to any one of claims 1 to 2, characterized in that: The steps include: (1) Magnesium powder and silicon-containing oxide are fully mixed and placed in a tube furnace, the tube furnace is heated to a specified temperature under an inert gas, and then a mixture of carbon dioxide and nitrogen is introduced to react, and after a certain period of time, the inert gas is switched and the temperature is lowered to obtain a black powder; (2) The black powder is immersed in an acidic solution, then washed with deionized water until it becomes neutral, and then dried to obtain the metal-free catalyst.
4. The preparation method according to claim 3, characterized in that: The heating rate of the tubular furnace is 2-20°C / min, and the reaction temperature is 600-800°C.
5. The preparation method according to claim 3, characterized in that: The inert gas is any one or more of helium and argon; a mixed gas of carbon dioxide and nitrogen is introduced into the tubular furnace for 0.2-10 hours.
6. The preparation method according to claim 3, characterized in that: The acidic solution is one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and perchloric acid. The molar concentration of the acidic solution is 0.5%-50%, the soaking temperature is 20-80° C., and the soaking time is 0.5-5h.
7. The preparation method according to claim 3, characterized in that: The drying temperature is 40-120° C., and the drying time is 2-48 hours.
8. Use of the metal-free catalyst according to any one of claims 1 to 2 or the metal-free catalyst prepared by the preparation method according to any one of claims 3 to 6 in acetylene hydrochlorination reaction.
9. The use according to claim 8, characterized in that The reaction temperature of the acetylene hydrochlorination reaction is 150-250°C, and the acetylene space velocity is 5-300h -1 , the molar ratio of hydrogen chloride to acetylene is 1:1-1.5:1.
Citation Information
Patent Citations
Preparation and application method of metal-free catalyst for fixed-bed acetylene hydrochlorination to vinyl chloride
CN108246340B
Preparation and application method of metal-free catalyst used for fixed bed acetylene hydrochlorinate preparation of vinyl chloride
CN108246340A
Hollow-structure tightly-combined high-performance silicon / graphitized carbon composite material and preparation method and application thereof
CN111313029A